2004
DOI: 10.5194/angeo-22-3995-2004
|View full text |Cite
|
Sign up to set email alerts
|

Multitaper spectral analysis of atmospheric radar signals

Abstract: Abstract. Multitaper spectral analysis using sinusoidal taper has been carried out on the backscattered signals received from the troposphere and lower stratosphere by the Gadanki Mesosphere-Stratosphere-Troposphere (MST) radar under various conditions of the signal-to-noise ratio. Comparison of study is made with sinusoidal taper of the order of three and single tapers of Hanning and rectangular tapers, to understand the relative merits of processing under the scheme. Power spectra plots show that echoes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…We used here three sinusoidal tapers. Such a method has been previously and successfully used for the analysis of climate time series of different time scale and resolution (Ghil and Vautard, 1991;Yiou et al, 1996;Ghil et al, 2002;Anandan et al, 2004;Kilcik et al, 2008;Vaquero et al, 2010). Since this method is now standard, and can be found elsewhere, we do not describe it here.…”
Section: Methodsmentioning
confidence: 97%
“…We used here three sinusoidal tapers. Such a method has been previously and successfully used for the analysis of climate time series of different time scale and resolution (Ghil and Vautard, 1991;Yiou et al, 1996;Ghil et al, 2002;Anandan et al, 2004;Kilcik et al, 2008;Vaquero et al, 2010). Since this method is now standard, and can be found elsewhere, we do not describe it here.…”
Section: Methodsmentioning
confidence: 97%
“…Though the MTM degrades the Doppler velocity resolution, it can reduce the spectrum perturbations without degrading the time resolution because the Doppler spectra produced by the orthogonal tapers have independent spectrum perturbations. Anandan et al [] reported that the MTM can improve echo detection in low SNR conditions.Because a huge amount of data needs to be processed in RIM measurements, we used the moment method. For methods that require iterations to calculate the spectral parameters (e.g., the least squares method), initial values of all the P , V d , and σ 3dB values and thresholds to finish the iterations must be determined.…”
Section: Computation Methods For the Spectral Parametersmentioning
confidence: 99%
“…Though the MTM degrades the Doppler velocity resolution, it can reduce the spectrum perturbations without degrading the time resolution because the Doppler spectra produced by the orthogonal tapers have independent spectrum perturbations. Anandan et al [2004] reported that the MTM can improve echo detection in low SNR conditions. 3.…”
Section: Radio Sciencementioning
confidence: 99%
“…This method has some parameters were utilized to adaptively fallow the radar signal within the range-Doppler spectral frame. Bi-spectral estimation [2] and Multi taper spectral estimation [3] is used to radar signal, which include broadened spectral peak and high computational cost respectively. Other algorithms like cepstral thresholding [4], wavelet-based denoising [5] and PCA approach [6] are also applied to spectrum estimation of the MST data.…”
Section: Introductionmentioning
confidence: 99%